Comparative Analysis on the Performance of Bluetooth 3.0 and Bluetooth 4.0 in the monitoring system of Toddler Growth - Teguh Martono, Kurniawan Martono (Jurnal Sistem Komputer, 2020)
The development of this toddler growth recorder was designed using HC 05 (bluetooth 3.0) module. Meanwhile, the development of the bluetooth protocol has reached bluetooth 4.0, one of the tools used by Bluno Nano board. This study aims to compare the performance of communication devices using HC 05 module (bluetooth 3.0) with Bluno Nano board (bluetooth 4.0). The data were collected through a number of tests with calculations using electrical formulas. The results obtained from the performance of these two tools showed that Bluno Nano (bluetooth 4.0) board had more advantages compared to HC 05 module.